LINGUISTIC FEATURES OF HUMAN NAMES IN ENGLISH AND UZBEK LANGUAGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This paper explores the linguistic features of human names in English and Uzbek languages, focusing on their cultural, historical, and sociolinguistic aspects. Names serve as essential markers of identity and cultural heritage, reflecting the linguistic and social structures of a community. This study highlights the structural differences, phonetic characteristics, and semantic connotations of names in these two languages. Additionally, it delves into the influence of historical events, cultural exchanges, and linguistic borrowing on the evolution of naming conventions. By comparing the two languages, the paper aims to provide a deeper understanding of how names embody linguistic diversity and cultural identity.